Technology assessment of cyber security in the Philippine Banking Industry - Ambrocio, Deah S.
The concept of cyber security in the Philippine Banking Industry took place when the banks started to drift away from traditional banking to digital banking. Digital banking refers to the usage of online and mobile platforms in offering banking products and services to the customers. The extensive use of technology by the Philippine banks resulted for them to be more exposed in the cyber space, hence in the cyber threats as well.